2002
DOI: 10.1126/science.1071884
|View full text |Cite
|
Sign up to set email alerts
|

Connections and Regulation of the Human Estrogen Receptor

Abstract: Estrogen regulates a plethora of functionally dissimilar processes in a broad range of tissues. Recent progress in the study of the molecular mechanism of action of estrogen(s) has revealed why different cells can respond to the same hormone in a different manner. Three of these findings are of particular importance: (i) There are two genetically and functionally distinct estrogen receptors that have distinct expression patterns in vivo; (ii) the positive and negative transcriptional activities of these recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
372
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(379 citation statements)
references
References 22 publications
1
372
1
4
Order By: Relevance
“…Estrogen is nonselective for the two receptors and the binding of estrogen results in a receptor-ligand complex that binds with high affinity to estrogen responsive elements (EREs) on DNA. Transcriptional regulation by the ERs may occur through a direct interaction of ERs with EREs or through an interaction of ER with other transcription factors (Sp1, AP-1 and NF-kB; McDonnell and Norris, 2002). The two receptors can heterodimerize, and they may modulate each other's effects (Gustafsson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen is nonselective for the two receptors and the binding of estrogen results in a receptor-ligand complex that binds with high affinity to estrogen responsive elements (EREs) on DNA. Transcriptional regulation by the ERs may occur through a direct interaction of ERs with EREs or through an interaction of ER with other transcription factors (Sp1, AP-1 and NF-kB; McDonnell and Norris, 2002). The two receptors can heterodimerize, and they may modulate each other's effects (Gustafsson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing estrogen levels or altering the activity of the receptor can induce these cancers to regress. E2 action involves ligand-mediated activation of nuclear ER-α and ER-β, which interact directly with estrogen response elements (EREs) in the promoter and/or enhancer regions of target genes and recruit various coactivators to mediate transcriptional regulation [3]. ER regulation is not limited to direct ligand binding.…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding to E2, ERa undergoes conformational changes facilitating cofactor binding and nuclear localization (McDonnell and Norris, 2002). Immunoprecipitation experiments showed that Per2 associates with ERa in 293T and MCF-7 cells, and E2 stimulation enhances the interaction (Figure 2a).…”
mentioning
confidence: 99%